PROGRAM TALI HATI UNTUK MENINGKATKAN KESIAPAN PERNIKAHAN DALAM HAL KOMUNIKASI PADA PASANGAN PRANIKAH - , Yunita Kurniawati; , Dra. Kwartarini W.Y., M.Med., Sc., Ph.D., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Communication is a major component of daily interaction process. Lack of communication can caused increasing divorced rate. Otherwise, communication also can increasing a quality of marriage. There is no program for couples to improve communication skills, especially for premarital couples. Tali hati Program is a couple communication skills program that include of self disclosure, understanding a goal setting of marriage, conflict resolution and communication skills in premarital couples.The purpose of this study was to investigate the effectiveness of Tali Hati Program to increasing the marriage readiness of communication in premarital couples. Subject in this study amounted to 10 of premarital couples, who are willing to follow the program, and they were devided to two groups, experimental group amount of five premarital couples and control group as a waitinglist group amount of five premarital couples. The experimental group completed a marriage readiness scales before (pre test) and after (post test) training, and follow up.This study were analyzed using Wilcoxon and Mann Whitney non parametrics test.The experiment found out the Mann Whitney test showed that number of Z=-2,720 with p=0,007 (p<0,01) and Wilcoxon showed Z=-1667 with p=0,096 (p>0,05). The result supported by qualitative analyzed, showed that Tali Hati Program can increasing marriage readiness of communication. Our findings suggest that Tali Hati Programs are generally effective to increasing marriage readiness of communication among premarital couples.